Prospective cohort study on injuries and health problems among circus arts students - Janine H Stubbe; Angelo Richardson; Rogier M van Rijn (BMJ Open Sport & Exercise Medicine, 2018)
Aim The amount of injuries, illnesses and mental health problems was calculated among circus arts students, using a method designed to capture more than just time-loss and/or medical injuries. Furthermore, injury incidence rate, injury incidence proportions, anatomical injury location and severity of injuries were assessed.Methods A total of 44 first-year, second-year and third-year circus arts students were prospectively followed during one academic year. Every month, all students were asked to complete questionnaires by using the online Performing Artist and Athlete Health Monitor, which includes the Oslo Sports Trauma Research Centre Questionnaire on Health Problems.Results In total, 41 students completed the entire follow-up period. The response rate was 82.9%. During the academic year, all (100%) students reported a health problem. A total of 261 health problems were reported consisting of 184 injuries (70.5%), 51 illnesses (19.5%), 15 mental problems (5.0%) and 11 other health problems (3.1%). The injury incidence rate was 3.3 injuries per 1000 hours (95% CI 2.7 to 3.9). Monthly incidence proportion for substantial injuries (ie, problems leading to moderate or severe reductions in training volume or in performance or complete inability to participate in activities) ranged from 6.8% to 34.1%. Shoulder (n=51; 27.7%), lower back (n=29; 15.8%), wrist (n=26; 14.1%) and ankle (n=17; 9.2%) were the most reported injuries. The average duration of the injuries was 6.9 days (median=2.0; SD=15.0).Conclusions We implemented a new registration method for circus artists, which captures a complete picture of the burden of health problems in circus students. Our study showed that the burden of injuries is high in this population.